ASSISTANCE FOR THE DEVELOPMENT OF HOTS (HIGHER ORDER THINKING SKILLS) PROBLEMS FOR IMPROVING THE PEDAGOGIC CAPABILITIES OF INDONESIAN TEACHERS OF HIGH SCHOOL IN ACEH TIMUR - Joko Hariadi; Azrul Rizki (Global Science Society, 2022)
This service aims to provide assistance and guidance for high school teachers in East Aceh Regency to prepare questions based on HOTS (Higher Order Thinking Skills). This community service activity aims to (1) assist teachers in increasing understanding of the evaluation of learning outcomes, (2) increase teachers' understanding of HOTS questions, and (3) improve teachers' pedagogical abilities in making HOTS questions, so that later HOTS questions are obtained in accordance with 2013 curriculum standards revision. This community service activity was carried out in the form of short training for four face-to-face meetings by complying with Health protocols and three online discussions through the Whatsapp group application. This activity was carried out at SMK Negeri 1 Peureulak, East Aceh Regency, which was attended by high school Indonesian language studies teachers in East Aceh Regency. The methods applied in the implementation of this activity are tutorial, discussion, simulation and demonstration methods. The result of the service from this activity is an increase in the teacher's understanding of HOTS (Higher Order Thinking Skills) questions and the teacher's ability to make HOTS (Higher Order Thinking Skills) questions.